2017
DOI: 10.1111/jasp.12454
|View full text |Cite
|
Sign up to set email alerts
|

Quick to the draw: How suspect race and socioeconomic status influences shooting decisions

Abstract: We examined the role of both suspect race and socioeconomic status (SES) on shooting decisions during a first‐person shooter task. Two studies revealed that both suspect race and SES influenced shooting decisions. Non‐Black participants shot armed high‐SES Black suspects faster than armed high‐SES White suspects and responded “don't shoot” faster for unarmed high‐SES White suspects than unarmed high‐SES Black suspects. No race differences appeared in the low‐SES conditions—responses resembled high‐SES Black su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 48 publications
(102 reference statements)
2
25
1
Order By: Relevance
“…Another possibility consistent with previously observed categorical associations between race and status ( Weeks and Lupfer, 2004 ; Penner and Saperstein, 2008 ; Freeman et al , 2011 ; Lei and Bodenhausen, 2017 ) is that race and status may interact during person evaluation ( Correll et al , 2011 ; Moore-Berg et al , 2017 ). Due to high-EMS perceivers’ anxiety about appearing prejudiced ( Amodio et al , 2006 ) and tendency to focus on non-racial attributes ( Norton et al , 2006 ; Apfelbaum et al , 2008 ), NAcc and VMPFC responses may evince a simultaneously enhanced evaluation of high-SES Black targets and a devaluation of high-SES White targets ( Bergsieker et al , 2010 ; Swencionis and Fiske, 2016 )—with the reverse pattern in amygdala activation.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another possibility consistent with previously observed categorical associations between race and status ( Weeks and Lupfer, 2004 ; Penner and Saperstein, 2008 ; Freeman et al , 2011 ; Lei and Bodenhausen, 2017 ) is that race and status may interact during person evaluation ( Correll et al , 2011 ; Moore-Berg et al , 2017 ). Due to high-EMS perceivers’ anxiety about appearing prejudiced ( Amodio et al , 2006 ) and tendency to focus on non-racial attributes ( Norton et al , 2006 ; Apfelbaum et al , 2008 ), NAcc and VMPFC responses may evince a simultaneously enhanced evaluation of high-SES Black targets and a devaluation of high-SES White targets ( Bergsieker et al , 2010 ; Swencionis and Fiske, 2016 )—with the reverse pattern in amygdala activation.…”
Section: Introductionsupporting
confidence: 87%
“…At present, there are few empirical studies examining the intersections of race and status in person evaluation (but see Jussim et al , 1987 ; Kirby, 1999 ; Moore-Berg et al , 2017 ). Addressing this gap in social neuroscience, the present research revealed that White perceivers’ EMS altered neural processing of a non-racial attribute (viz., status) during person evaluation, independently of race.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, participants demonstrate more shooter bias toward rich Blacks than rich Whites and no significant differences in shooting decisions between poor Whites and poor Blacks. Thus, participants respond similarly toward poor Whites, poor Blacks, and rich Blacks and uniquely toward rich Whites (Moore‐Berg, Karpinski, & Plant, ). This pattern of results mirrors other shooter bias research that alters suspect race and the type of neighborhood (i.e., dangerous or safe) that the suspect is shown in (Correll, Wittenbrink, Park, Judd, & Goyle, ).…”
Section: An Intersectional Approach To Race and Social Classmentioning
confidence: 99%
“…Relatedly, physical fatigue – as operationalized by sleep – also had a negative effect on shooting accuracy (Ma et al, 2012). Although a large body of work on police shooting decisions has focused on the difference between Black vs. White targets, some scholars have begun examining the role of gender, SES, and other racial and ethnic backgrounds (e.g., Latino, Asian, Muslim: Fleming et al, 2010; Plant et al, 2011; Sadler et al, 2012; Moore-Berg et al, 2017).…”
Section: Dynamic Accumulation Of Evidence In the Decision To Shoot Ormentioning
confidence: 99%